EDUCATING SOCIETY: ASSOCIATIONS METHOD AND PARTICIPATORY PLACE BRANDING - Murinska, Sandra; Pozņakovs, Kārlis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Places like people have their own image now. It is best to be there, to live there and consume all what this place can afford. In theoretical literature this is characterized as an competition between places to be leaders in marketplaces. Places include more and more efforts on techniques and methods in their governing philosophy. Place branding is a planned activity that describes the city as an appropriate environment for living, working, shopping, leisure. While for already known places it is just rebranding or improving existing image, many local places are doing it for the first time to be competitive.This paper analyzes the use of associations method in building brand of the places. Research is based on two case studies on towns in Latvia – Rezekne and Preili. The purpose of this article is to find out how a city brand can be created using the associations method. Based on the analysis of stakeholders’ associations, the effectiveness of associations is described.